Mobilizing grid flexibility through optimal transmission switching for power systems with large‐scale renewable integration. (21st November 2019) - Numan, Muhammad; Feng, Donghan; Abbas, Farukh; Habib, Salman; Rasool, Aazim
Summary: In order to cope with the challenge of reducing CO2 emissions concerning climate change, many countries are increasing their renewable energy sources (RES) shares in their power system networks. However, the existing transmission network is not planned to accommodate such a large‐scale integration of RES. Therefore, the need for new transmission topologies to better utilize the existing transmission infrastructure is more demanding to be practically implemented. In this paper, optimal transmission switching (OTS) is incorporated in a generic two‐stage stochastic unit commitment (SUC) problem with high penetration of wind power generation. The problem is modeled as a mixed integer programming problem (MIP). To reduce the computational complexity for solving the MIP, a warm‐start strategy is proposed to assist CPLEX in finding the optimal solution in a reasonable amount of time. Numerical tests are conducted on the modified IEEE 6‐bus and 118‐bus systems to validate the effectiveness of the optimization problem incorporating OTS in SUC problem. Using the standard IEEE 118‐bus system, an extensive economic and computational analysis is performed to characterize OTS effect on total system operating cost, sensitivity to variation in load, and transmission line congestion. Test results validate that system operating cost can be reduced up to 8% as compared with generic SUC problem without transmission switching.